Kemitraan Pemerintah Dengan Publik-Swasta (PPP) dalam Pembangunan Infrastruktur Berkelanjutan di Indonesia - Pahripi, Muhammad Riza; Mahyuni, Mahyuni (IAI Nasional Laa Roiba Bogor, 2025)
The successful implementation of PPP in Indonesia will depend on regulatory strengthening, effective risk management, and careful consideration of ethical aspects. Sustainable capacity building and coordination between stakeholders are key in maximizing the potential of PPPs to meet Indonesia's infrastructure needs This study uses a qualitative method with a case study approach to analyze Public-Private Partnerships (PPPs) in Sustainable Infrastructure Development in Indonesia. The qualitative research method was chosen because it allows the exploration of complex social phenomena. Data is collected through document studies with the aim of analyzing journals and reports of research results and related documents. PPP optimization strategies for sustainable development require a comprehensive approach that includes several key aspects. One of the key strategies is the integration of sustainable development principles into the PPP framework, which includes good governance, stakeholder participation, and adherence to ethical standards 1. Integration of sustainability principles in all stages of the project, with a focus on good governance 2. KPI-based performance measurement to ensure the sustainability of the project lifecycle 3. Innovative approaches such as system dynamics models to manage sustainability challenges. 4. Balanced distribution of investment between the public and private sectors to drive sustainability performance.